Visual Analysis of Importance and Grouping in Software Dependency Graph - Pich, Christian; Nachmanson, Lev; Robertson, George G. (SoftVis '08 Proceedings of the 4th ACM symposium on Software visualization, 2008)
Understanding dependencies between components is a key task in software engineering. We present a method for the display and visual analysis of dependency graphs occurring in large software systems. Our layout approach takes into account similarity and importance of the system components and additional grouping information; using efficient algorithms based on linear algebra, it scales to very large dependency graphs. We apply our method to two real-world software systems and present the results.